“Who does not kill hogs will not get black puddings” – Parasitism and Parasite in Soviet Society (based on the materials of the Daugavpils City Prosecutor’s Office and the city press (1953–1964)) - Krylova, Iveta (Acta humanitarica academiae Saulensis, 2019)
In the Soviet period, also called “Khrushchev thaw” (1953–1964), in the territory of Latvia, in the Soviet society it was actively fought against parasitism as a way of life of any person, who without justifiable reasons was not working for the benefit of the Soviet state. The struggle against parasitism, codified by the normative acts of the USSR, also had a clearly expressed ideological character. “Who does not kill hogs will not get black puddings” – a popular slogan of the Soviet era, pressing to a struggle against any manifestation of parasitism as a parasitic existence at the expense of society. A parasitism or parasite in Soviet society was any woman ranging from women with pronounced marginal behavior (tramps, women with alcohol addiction, thieves, fraudsters, women of deviant sexual behavior), underground business leaders to housewives who care only about their family and children. The article investigates the problem of female parasitism in the Soviet and in the Latvian society of that historical period in the city Daugavpils.The basis of the investigation are the materials of the prosecution cases of the Daugavpils Regional State Archive of the Latvian National Archive (DZGA LNA), 875 fund, inventory number 1 as well as the publications in the press of Daugavpils: annual issues between 1953 and 1964 “Padomju Daugava” and “Red Banner”.The materials of the prosecutor’s office are used as the sources for the recreation of the parasitism as a social phenomenon of the past. The analysis covers a deep and fully showdown of facts of the existence of these women and social reasons that pushed them to the life image that was called parasitism during the Soviet era. The reflection of the Daugavpils city press about the problem of female parasitism deepens the idea of the causes and manifestations of female parasitism in Soviet society as well as the opposition to this phenomenon of the Soviet regime and society.
Keywords: Daugavpils city; woman; press; Daugavpils city Prosecutor’s Office; Soviet period; parasitism; parasite